Identification and Functional Analysis of Three NlCstF Genes in Nilaparvata lugens - Shengli Jing; Feifei Wang; Aobo Ren; Fang Zheng; Bingbing Yu; Jingang Xu; Yali Liu; Jing Yang; Ruixian Chen; Wei Zeng; Yimei Zhang; Danxia Ke; et al. (Insects)
The Cleavage Stimulation Factor (CstF) complex, consisting of three subunits, is essential for the 3′ end processing of precursor messenger RNA (pre-mRNA). In mammals, this complex includes CstF50, CstF64, and CstF77, named according to their molecular weights, and these proteins are conserved across many organisms. However, the functional roles of the three CstF genes (NlCstF50, NlCstF64, and NlCstF77) in Nilaparvata lugens, a major rice pest, have not been fully explored. This study identified and characterized the sequences of these genes, with proteins encoded by NlCstF50, NlCstF64, and NlCstF77 consisting of 439, 419, and 732 amino acids, respectively. These proteins are conserved among various insect species. Spatio-temporal expression analysis revealed that these genes are expressed at all developmental stages and in various tissues, with peak levels in eggs and testes. RNA interference (RNAi) targeting one or all three NlCstF genes resulted in a reduction in gene expression by 68% to 90% at 72 h post-injection, indicating that multi-gene dsRNA can achieve similar silencing outcomes as single-gene dsRNA. Knocking down one or all three NlCstF genes caused significant lethal phenotypes and molting disruptions. Mortality rates increased from 62.5% (dsNlCstF50) to 95.4% (dsNlCstF(50+64+77)). Additionally, silencing these genes reduced the number of eggs laid per female and hatch rates. These results highlight the critical role of NlCstF genes in the development and reproduction of N. lugens, suggesting their potential as targets for RNAi-based pest control strategies.